Anxiolytic effect of zinc oxide gallic acid composite nanoparticles following D-galactose administration in rats - Noreen Samad; Arslan Khalid; Natasha Manzoor; Bakar Bin Khatab Abbasi; Umer Ejaz; Ayesha Ahmad Sumra; Tahira Saleem; Mohammad Raish; Ali Irfan; Yousef A. Bin Jardan (Scientific Reports)
Abstract D-galactose by instigating oxidative stress, inflammation, and degenerative changes, causes neurological problems, i.e., anxiety. Zinc oxide (ZnO)-gallic acidNPs were used to evaluate behavioral, biochemical, neurochemical, and histopathological studies following D-galactose administration in rats. Thirty animals were alienated into five sets (n = 6) i.e., control, D-galactose (300 mg/kg/mL), D-galactose + gallic acid (50 mg/mL/kg), D-galactose + ZnONPs (10 mg/mL/kg), and D-galactose + ZnO-gallic acidNPs (10 mg/mL/kg). For 28 days, the animals were given their respective treatments intraperitoneally once a day. The anxiety-like behavior was evaluated following the treatment period using behavioral tests, i.e., light–dark and elevated-plus-maze activities. The hippocampus was isolated for biochemical, neurochemical, and histopathological studies. Results showed that ZnO-gallic acidNPs normalize the anxiety-like behavior induced by D-galactose administration. D-galactose induced a reduction in the activity of antioxidant enzymes (superoxide dismutase, catalase, and glutathione peroxidase), increased oxidative-stress markers (malondialdehyde), and elevated inflammatory markers (interleukin-1 and tumor necrosis factor-α). It also impaired serotonergic metabolism and the responsiveness of 5-HT1A receptors, along with causing morphological alterations in the hippocampus. ZnO-gallic acidNPs prevented these effects. These results underscore the protective effects of ZnO-gallic acid NPs against D-galactose-induced negative influences. The present finding suggested that ZnO-gallic acidNPs may be used as a potential agent to treat D-galactose-induced psychiatric illnesses such as anxiety through their antioxidant, anti-inflammatory, and neuromodulatory potential.